Embedded systems firmware demystified - Sutter, Ed (Distributed in the U.S. and Canada by Publishers Group West, 2002)
Show how to program embedded software systems, build a platform where an embedded system application can reside, and startup an embedded system project. The author covers exception handling, flash memory drivers, a flash file system, and serial and Ethernet connections. A familiarity with C is assumed. The CD-ROM contains the monitor package described in the book and Microcross GNU X-Tools.